Financial sustainability of cross-border e-commerce of small medium enterprises in Chongqing, China / Zhao Mingying, Wen Shunmin and Amrizah Kamaluddin - Zhao, Mingying; Wen, Shunmin; Kamaluddin, Amrizah (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2023)
Chongqing Province in China is a comprehensive pilot area for cross-border e-commerce. Although the government has issued several policies to promote cross-border e-commerce, the cycle of cross-border e-commerce in Chongqing is short, and the experience in various aspects is not yet mature. This study, based on resource-based theory, explores the factors that influence the financial sustainability of cross-border e-commerce in the face of COVID-19 from the perspective of small and medium-sized enterprises (SMEs) managers in Chongqing Province, China. The data were collected through a questionnaire survey to gauge whether government support, innovation, and the usage of e-commerce platforms have impacted the financial sustainability of cross-border e-commerce for Chinese SMEs. One hundred and fifty-seven sample data were analyzed according to correlation analysis, regression analysis, and hypothesis testing. The results indicate a significant relationship between government support, innovation, the usage of e-commerce platforms, and financial sustainability. This study confirms the importance of national policies for the financial sustainability of small and medium-sized cross-border e-commerce enterprises. The use of cross-border e-commerce platforms should improve their comprehensive service capabilities and supply chain management. Thus, it enhances financial sustainability. Also, it may promote China's cross-border e-commerce enterprises to play a greater role in foreign trade and achieve new growth in economic innovation and development.